KECERDASAN EMOSIONAL DAN KEPEMIMPINAN KEPALA SEKOLAH SEBAGAI PREDIKTOR TERHADAP KINERJA GURU SMP NEGERI SEKECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Lasmaria Silalahi; Suarman Suarman; Dudung Burhanuddin (Universitas Riau, 2017)
This study aims to investigate the influence of variables (1) of emotionalintelligence on the performance of teachers, (2) the leadership of principals on teacherperformance, (3) emotional intelligence and leadership principals together on teacherperformance. Respondents were teachers Junior High School in the District of Peace MarpoyanPekanbaru totaling 114 individuals obtained by stratified random sampling technique. Datacollected through questionnaire as a research instrument. Analysis of the data used is theanalysis of the profile of respondents, descriptive analysis, inferential statistical analysis andhypothesis testing. Instrument reliability coefficient is calculated using Cronbach alpha. In thepartial results show the positive influence of emotional intelligence on the performance of teachers0.603, and there are positive influence between the leadership of the principal on teacherperformance of 0.635. While simultaneously the influence of emotional intelligence and leadershipprincipals on teacher performance of 0.698.